Palladium-catalyzed carbene coupling of N-tosylhydrazones and arylbromides to synthesize cross-conjugated polymers. Issue 5 (10th January 2019) - Zhou, Qi; Gao, Yunpeng; Xiao, Yiyang; Yu, Lefei; Fu, Zihao; Li, Zichen; Wang, Jianbo
Abstract : Palladium-catalyzed cross-coupling reactions of N -tosylhydrazones and arylbromides have been applied for the first time in the synthesis of cross-conjugated polymers, namely poly(arylene-1, 1-vinylidene)s (iso-PAVs). Abstract : Carbene-involving cross-coupling reactions of N -tosylhydrazones and arylbromides have been introduced into polymer chemistry for the first time, providing a novel method to access a new type of cross-conjugated polymer, poly(arylene-1, 1-vinylidene)s (iso-PAVs). The pendant double bonds of these cross-conjugated polymers allow for further post-polymerization functionalization. The good thermal stability and remarkable optical properties of these cross-conjugated polymers reveal their potential for applications.